Inovasi Desain Pembelajaran PAI Berbasis Teknologi untuk Meningkatkan Motivasi Siswa - Sofiah Harahap; Aditya Warman; Gusmaneli (Indo Publishing, 2025)
This study aims to develop and analyze innovations in the learning design of Pendidikan Agama Islam (PAI) using technology, with a focus on enhancing student motivation. The innovative learning design integrates various digital media such as interactive videos, educational applications, and online platforms tailored to PAI content. The research employs a qualitative approach with case studies conducted in several secondary schools in both urban and rural areas to evaluate the effectiveness of technology use in different contexts. Data were collected through observations, interviews, and motivation questionnaires administered before and after the learning process. The findings reveal that incorporating technology significantly increases students’ interest and active participation during lessons. Moreover, students demonstrated improved understanding of religious concepts and the ability to apply Islamic values in daily life. The use of digital media also created a more engaging and interactive learning environment, reducing boredom associated with traditional teaching methods. This study highlights the importance of innovating PAI learning design to align with technological advancements and the characteristics of the current generation. It recommends that educators and educational institutions systematically integrate technology in curriculum planning and learning activities to achieve optimal learning outcomes and foster holistic character development in students.